A Review of the Ethnobotany, Phytochemistry and Medicinal Properties of Australian Terminalia Species - Zai, Muhammad Jawad Yousaf; Cheesman, Matthew James; Cock, Ian Edwin (Pharmacognosy Communications)
The genus Terminalia contains some of the most widely used plants in traditional medicine. Many species possess antifungal, antibacterial, antiviral, antiprotozoal, analgesic, antidiarrheal, antioxidant, antimalarial, anticancer, and anti-inflammatory properties. Some species also have cardiovascular and wound-healing effects. Despite their myriad of traditional uses, relatively few studies have examined the medicinal properties and phytochemistry of most Australian Terminalia spp. The high tannin content of Terminalia spp. has been postulated to be a major contributor to the medicinal properties of this important genus. However, the complexities of tannins are generally believed to make them a poor choice for drug design. Therefore, much of the interest in Terminalia species has been for their nutraceutical and pharmacognostic value, and they remain under-explored in terms of drug discovery. Recent studies have identified many other important phytochemicals within Terminalia species apart from the tannins and have established that these compounds may contribute to their therapeutic bioactivities. Several Australian Terminalia species (particularly Terminalia carpentariae C.T.White, Terminalia catappa L., Terminalia ferdinandiana Exell and Terminalia grandiflora Benth) have received the most attention due to their reported high antioxidant contents. In contrast, other Australian Terminalia spp. have been relatively ignored. This review discusses recent studies into the phytochemistry, medicinal properties and the underlying therapeutic mechanisms of Australian Terminalia species to help direct future areas of research into this important genus.
Keywords: Australian Terminalia; Medicinal plant; Antioxidant; Anticancer; Antiinflammation; Antimicrobial.